Deletion of Smgpi1 encoding a GPI‐anchored protein suppresses sterility of the STRIPAK mutant ΔSmmob3 in the filamentous ascomycete Sordaria macrospora. Issue 4 (26th May 2015) - Frey, Stefan; Lahmann, Yasmine; Hartmann, Thomas; Seiler, Stephan; Pöggeler, Stefanie
Summary The striatin interacting phosphatase and kinase (STRIPAK) complex, which is composed of striatin, protein phosphatase PP2A and kinases, is required for fruiting‐body development and cell fusion in the filamentous ascomycete Sordaria macrospora. Here, we report on the interplay of the glycosylphosphatidylinositol (GPI)‐anchored protein SmGPI1 with the kinase activator SmMOB3, a core component of human and fungal STRIPAK complexes. SmGPI1 is conserved among filamentous ascomycetes and was first identified in a yeast two‐hybrid screen using SmMOB3 as bait. The physical interaction of SmMOB3 and SmGPI1 was verified by co‐immunoprecipitation. In vivo localization and differential centrifugation revealed that SmGPI1 is predominantly secreted and attached to the cell wall but is also associated with mitochondria and appears to be a dual‐targeted protein. Deletion of Smgpi1 led to an increased number of fruiting bodies that were normally shaped but reduced in size. In addition, Smmob3 and Smgpi1 genetically interact. In the sterile ΔSmmob3 background deletion of Smgpi1 restores fertility, vegetative growth as well as hyphal‐fusion defects. The suppression effect was specific for the ΔSmmob3 mutant as deletion of Smgpi1 in other STRIPAK mutants does not restore fertility.